Kedudukan dan Peran Panitera Pengganti dalam Mendukung Jalannya Persidangan di Pengadilan Tata Usaha Negara Banjarmasin - Muhamad Lexsi Pratama; Agita Naysilla Putri; Dewi Astuti; Muhammad Fery Syahputra; Wava Aulia Safari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to juridically and normatively examine the position and role of Substitute Clerks in supporting court proceedings at the Banjarmasin State Administrative Court (PTUN Banjarmasin). The method used is a normative legal approach by analyzing various laws and regulations governing the judicial system and the clerkship. Findings show that the Substitute Clerk holds a strategic position as a functional official bridging the judicial and administrative dimensions of the court process. The primary roles of a Substitute Clerk include assisting judges, recording court proceedings in the Court Minutes (BAS), conducting case minutation, and managing data through the Case Tracking Information System (SIPP). The implications of this study emphasize that the professionalism of Substitute Clerks is crucial in realizing the principles of simple, fast, and low-cost justice, as well as ensuring legal certainty through accountable administrative order.